2022
DOI: 10.1021/jacs.2c02818
|View full text |Cite
|
Sign up to set email alerts
|

Palladium Terminal Imido Complexes with Nitrene Character

Abstract: Whereas triplet-nitrene complexes of the late transition metals are isolable and key intermediates in catalysis, singlet-nitrene ligands remain elusive. Herein we communicate three such palladium terminal imido complexes with singlet ground states. UV–vis–NIR electronic spectroscopy with broad bands up to 1400 nm as well as high-level computations (DFT, STEOM-CCSD, CASSCF/NEVPT2, EOS analysis) and reactivity studies suggest significant palladium(0) singlet-nitrene character. Although the aliphatic nitrene comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 42 publications
0
17
0
1
Order By: Relevance
“…Accordingly, based on the recently reported tris -[2-(3-mesityl- im idazole-2-ylidene)- m ethyl]­ami n e (TIMMN Mes ) chelate, we herein present two comprehensive series of mid- to high-valent iron alkyl imido complexes in oxidation states ranging from +II to +V. The relative instability of the Fe­(V) adamantyl imide leadsto the best of our knowledgeto an unprecedented C–N bond cleavage, thus providing an alternative route to the recently reported Fe­(V) nitrido complex, originally synthesized via azide photolysis of [(TIMMN Mes )­Fe II (N 3 )] + and subsequent oxidation of its Fe­(IV) nitride precursor . The complex [(TIMMN Mes )­Fe IV (N)] + ( 7 ) + , in turn, can be derivatized in an N–C bond alkylation reaction, thereby providing an alternative route to primary alkyl imides.…”
Section: Introductionmentioning
confidence: 97%
“…Accordingly, based on the recently reported tris -[2-(3-mesityl- im idazole-2-ylidene)- m ethyl]­ami n e (TIMMN Mes ) chelate, we herein present two comprehensive series of mid- to high-valent iron alkyl imido complexes in oxidation states ranging from +II to +V. The relative instability of the Fe­(V) adamantyl imide leadsto the best of our knowledgeto an unprecedented C–N bond cleavage, thus providing an alternative route to the recently reported Fe­(V) nitrido complex, originally synthesized via azide photolysis of [(TIMMN Mes )­Fe II (N 3 )] + and subsequent oxidation of its Fe­(IV) nitride precursor . The complex [(TIMMN Mes )­Fe IV (N)] + ( 7 ) + , in turn, can be derivatized in an N–C bond alkylation reaction, thereby providing an alternative route to primary alkyl imides.…”
Section: Introductionmentioning
confidence: 97%
“…The Ni−N bond length may reflect the continuum between nickel imido resonance structures. 76,77 The structure of 5a also features a π-arene interaction (Ni−C40 and Ni−C41 bond lengths = 2.038(2) and 2.114(2) Å, respectively). This interaction We found that the tether length to the appended borane has large effects on reactions with aryl azides.…”
Section: ■ Introductionmentioning
confidence: 70%
“…Similar to redistributing charge over more than one metal site, we propose that the B–N interaction (B–N bond length 1.567(3) Å) elongates the Ni–N bond in a manner that resembles a bridging mode. The Ni–N bond length may reflect the continuum between nickel imido resonance structures. , The structure of 5a also features a π-arene interaction (Ni–C40 and Ni–C41 bond lengths = 2.038(2) and 2.114(2) Å, respectively). This interaction imposes a bent Ni–N1–C40 bond (bond angle 75.40(14)°), which is distinct from that in Hillhouse’s imido complex (bond angle = 180°) .…”
Section: Resultsmentioning
confidence: 99%
“…4) Die Gruppe Munz synthetisierte und stabilisierte eine Imidoverbindung mit ausgeprägtem Singulett-Carbencharakter; dazu nutzten sie einen Palladium(0)komplex (Abbildung 2c). 5)…”
Section: Nebengruppen Und Koordinationschemieunclassified